Colorectal cancer screening uptake over three biennial invitation rounds in the English bowel cancer screening programme. Issue 2 (7th May 2014) - Lo, Siu Hing; Halloran, Stephen; Snowball, Julia; Seaman, Helen; Wardle, Jane; von Wagner, Christian
Abstract : Objective: To examine patterns of colorectal cancer (CRC) screening uptake over three biennial invitation rounds in the National Health Service (NHS) Bowel Cancer Screening Programme (BCSP) in England. Methods: We analysed data from the BCSP's Southern Hub for individuals (n=62 099) aged 60–64 years at the time of first invitation to screening with a follow-up period that allowed for two further biennial invitations. Data on sex, age and a neighbourhood-level measure of socioeconomic deprivation were used in the analysis. Outcomes included uptake of guaiac-based faecal occult blood (gFOB) test screening, inadequate gFOB screening (≥1 test kit(s) returned but failed to complete further gFOB tests needed to reach a conclusive test result), test positivity, compliance with follow-up examinations (usually colonoscopy) and diagnostic outcomes. Results: Overall gFOB uptake was 57.4% in the first, 60.9% in the second and 66.2% in third biennial invitation round. This resulted in 70.1% of the initial cohort having responded at least once, 60.7% at least twice and 44.4% three times. Participation in the first round was strongly predictive of participation in the second round ('Previous Responders': 86.6% vs 'Previous Non-Responders': 23.1%). Participation in the third round was highest among 'Consistent Screeners' (94.5%), followed by 'Late Entrants' (78.0%), 'Dropouts' (59.8%) and 'Consistent Non-Responders' (14.6%). Socioeconomic inequalities in uptake were observed across the three rounds, but sex inequalities decreased over rounds. Inadequate gFOB screening was influenced by screening history and socioeconomic deprivation. Screening history was the only significant predictor of follow-up compliance. Conclusions: Screening history is associated with overall gFOB uptake, inadequate gFOB screening and follow-up compliance. Socioeconomic deprivation is also consistently associated with lower gFOB uptake and inadequate gFOB screening. Improving regular screening among identified 'at-risk' groups is important for the effectiveness of CRC screening programmes.